S-deoxydihydroglyparvin from Glycosmis parva inhibits lipopolysaccharide induced murine macrophage activation through inactivating p38 mitogen activated protein kinase - Chanyanuch Laprasert; Chaisak Chansriniyom; Wacharee Limpanasithikul (Wolters Kluwer Medknow Publications, 2021)
Macrophages play major roles to produce several pro-inflammatory and inflammatory mediators in chronic inflammatory diseases. All current anti-inflammatory drugs target these mediators to alleviate inflammation. Searching for new anti-inflammatory agents is always needed due to problems from the clinical use of current anti-inflammatory drugs. We intended to evaluate the anti-inflammatory potential of three main compounds, arborinine, methylatalaphylline, and S-deoxydihydroglyparvin (DDGP), from Glycosmis parva leaves and branches on macrophage stimulated by lipopolysaccharide (LPS). Only DDGP demonstrated a potent inhibitor of LPS-activated macrophages. Results indicated that the mRNA level of inducible nitric oxide synthase (iNOS) was inhibited by the treatment in accompany with the decreased nitric oxide (IC50 at 3.47 ± 0.1 μM). DDGP was shown to suppress tumor necrosis factor-α, interleukin (IL)-1, and IL-6 at the mRNA expression and at the released protein levels. In addition, DDGP inhibited the several chemokines, monocyte chemoattractant protein-1 and macrophage inflammatory proteins-1α, and enzymes for prostaglandin (PG) synthesis. It also inhibited PGE2 production. On LPS signaling pathways, DDGP profoundly decreased phosphorylation of p38 mitogen-activated protein kinase (MAPK) in the LPS-treated cells. It had little or no effect on the activation of JNK, ERK and nuclear factor kappa B. In conclusion, results suggested that DDGP from G. parva inhibited expression and production of inflammatory molecules in LPS-activated macrophages through suppressing p38 MAPK activation. DDGP should be a good candidate anti-inflammatory agent in the future.